Hubungan Tingkat Pengetahuan Tentang Personal Hygiene Dan Persepsi Remaja Dengan Pencegahan Keputihan (Flour Albus) Di Smkn 03 Kota Bengkulu Tahun 2024 - Lince, Lili Sri; Handayani, Tita Septi; Murwati, Murwati (Universitas Dehasen Bengkulu, 2025)
More than 70% of women in Indonesia suffer from vaginal discharge caused by fungi and parasites such as pinworms or Trichomonas vaginalis, primarily due to humid weather conditions that trigger Candida albicans infections. The objective of this study is to investigate the relationship between knowledge levels regarding personal hygiene and adolescents' perceptions with the prevention of vaginal discharge (flour albus) at SMKN 03 Kota Bengkulu in 2024. The research method used was a descriptive study with a cross-sectional approach. The sampling technique employed was stratified random sampling, with a sample size of 88 female adolescents at SMKN 03 Kota Bengkulu. The results of the univariate analysis showed that some respondents (43.2%) had adequate knowledge, most respondents (64.8%) had positive perceptions, and most respondents (61.4%) had positive prevention of vaginal discharge (flour albus). The bivariate analysis revealed a significant association between the level of knowledge about personal hygiene (p=0.000) and adolescent perceptions (p=0.000) with the prevention of vaginal discharge (flour albus). There is a relationship between the level of knowledge about personal hygiene and adolescent perception with the prevention of vaginal discharge (flour albus) at SMKN 03 Kota Bengkulu in 2024. The researcher suggests that the results of this study can increase respondents' knowledge about vaginal discharge and how to prevent it. Providing information about the importance of personal hygiene in maintaining genital hygiene.